THE EFFECT OF FEE AND MOTIVATION ON CORRUPTION ERADICATION USING KPK PERFORMANCE AS THE INTERVENING VARIABLE - Eko Gumaya Sari; Dede Rahmat; Sofyan Widjaya (Asia Pacific Fraud Journal, 2020)
This research aims to find out the effect of fee and motivation on the eradication of corruption. Rewarding or giving fees has been set in Government Regulation Number 43 of 2018 concerning procedures for involving community participation and awarding in the prevention and eradication of criminal acts of corruption. Based on the Government Regulation No. 43 of 2018, those who provide information to law enforcers regarding allegations of corruption will get awards in the form of charter and premiums, or also called fees/rewards, ranging up to a maximum of IDR 200 million. In addition, certain motivation will also influence community to play a role in eradicating corruption.This research uses qualitative data or primary data obtained through questionnaires distributed to the public, economic observers, and practitioners. Data testing is done using Data Path analysis with Smart PLS. The number of valid and reliable sample data to be analyzed is as many as 40 samples. The results of this research show that fees/rewards have a positive and significant effect on corruption eradication. Motivation has a negative and not significant effect on corruption eradication. The variable of fees/rewards has a positive effect on corruption eradication mediated by the KPK performance. Motivation has a negative effect on corruption eradication mediated by the KPK performance. In this digital era,with super-sophisticated technology, the millennia generation has a very critical mindset in assessing the performance of the KPK. The Corruption Eradication Commission (Indonesia: Komisi Pemberantsan Korupsi/KPK), however, can provide confidence to the public that the community participation will make it easy for the KPK to carry out its work.